The closure of police stations leads to an increase in theft crime - Sebastian Blesse; André Diegmann (EconPol Forum, 2023)
Regional access to local police infrastructure matters for crime outcomes, Exploiting a police reform, we show that closing police stations increases car theft and residential burglary. Our findings are consistent with lower deterrence due to a lower visibility of the local police. Police closures lead local private security firms to exit the market, which exacerbates local crime. Fewer visible local police stations have severe and unintended consequences which need to be considered by bureaucrats and policy makers pushing for more efficiency in providing public safety
Keywords: 330